Kant’s Aesthetic Theory - Kemal, Salim. author. aut Link
VI, 197 p.
Keywords: In this accessible yet authoritative book, the author explains the argument and strategy of Kant's analysis of beauty. He clarifies the nature of aesthetic claims, examines the scope of Kant's justification of their validity, and shows how these lead Kant to investigate the relationship between beautiful objects, morality, and subjects. In the course of his discussion, the author links Kant's theory to contemporary commentaries, including those by Donald Crawford, Jacques Derrida, Paul Guyer, Rudolph Makkreel, Mary McCloskey, and Kenneth Rogerson.